Population structure and genetic diversity in wild dotted gizzard shad (Konosirus punctatus) revealed by microsatellite markers - Liu, Bingjian; Li, Jiasheng; Zhang, Kun; Peng, Ying; Liu, Yifan; Jin, Xun; Zheng, Sixu; Wang, Yunpeng; Liu, Liqin; Lü, Zhenming; Zhang, Shufei; Gong, Li (Frontiers in Marine Science, 2022)
Uncovering the fine-scale genetic structure has been long recognized as a key component in policymaking for the management of marine fisheries. Many species of Clupeiformes have suffered declines owing to overexploitation and habitat destruction. In this study, twenty polymorphic microsatellite markers were used to evaluate the genetic diversity and population structure of Konosirus punctatus, a pelagic fish of economic and ecological importance in the Northwestern Pacific Ocean. Although most of the variance occurred within individuals, significant differentiation (FST = 0.00384~0.19346) was shown in wild K. punctatus populations. Population structure analyses revealed five genetically divergent clades in K. punctatus in the Northwestern Pacific. Significant isolation by distance and one potentially outlier locus were revealed in K. punctatus, suggesting that interactions between historical climate shifts and environmental factors may contribute to the present-day genetic architecture. In summary, these results provided new perspectives on the population genetic structure of K. punctatus, facilitating the development of effective management strategies for this species.